A brief exposure to low pH prior to refrigerated storage reduces the motility and viability of goldfish sperm (Carassius auratus, Linnaeus, 1758). (June 2015) - Chantzaropoulos, A.; Nathanailides, C.; Kokokiris, L.; Barbouti, A.; Zhang, T.
Summary: Optimal conditions of short‐term storage of fish sperm are important for successful artificial reproduction protocols or incubation of sperm in a cryoprotecting medium for successful sperm cryopreservation. The influence of acid or alkaline incubating conditions on short term storage of goldfish sperm was investigated in a series of experiments. Goldfish sperm was diluted an immobilizing solution (1 : 3) and incubated for 1 h in acidic, pH 6.5 (AC group) or alkaline, pH 8.5 (AL group) conditions. Subsequently, the sperm of both groups was further diluted (1 : 3) in the immobilizing solution and the pH was adjusted to pH 7.51 (±0.02) and 7.56 (±0.07) in the AC and AL group respectively. The samples were kept in sealed bags and stored at 4°C. Viability (%) and motility (%) was estimated in samples obtained daily for the next 4 days. The results indicate that even a brief exposure of sperm to acid acidic conditions prior to storage accelerated the decline of sperm viability and motility during refrigeration.